The natural history of perianal disease. (13th March 2011) - Hayee, B; Sayer, V E; Kabir, M; Papagrigoriadis, S; Chung-Faye, G; Bjarnason, I; Forgacs, I
Abstract : Introduction: Perianal disease (PD; uncomplicated abscess and/or fistula) is a relatively common condition. There is a recognised association with Crohn's disease (CD) and 11–26% of patients in paediatric1 and adult2 case series are purported to develop intestinal CD. However, the temporal relationship is unclear, as is the natural history of PD. Methods: This was a single-centre (KCH) retrospective study with cohorts of patients having undergone medical or surgical therapy for PD since Jan 2008 (all after MRI) identified from theatre and electronic patient record databases (Galaxy and Unisoft). Case notes were then examined for the history, nature and length of follow-up of PD. Details of medical treatment were also obtained for patients with CD. Results: 97 patients (24 F; 37.5±12.4 years) were identified with uncomplicated PD (having undergone surgical intervention), with 158 episodes of perianal sepsis, most frequently occurring in relation to an intersphincteric (34/97) or transphincteric (27/97) fistula. Median follow-up was 7.4 months (IQR 2.3–20.6). Of these, 8 patients (4 F; 25.4±11.6 years) went on to develop histologically proven intestinal CD, with a median time from presentation with PD of 4.3 (3.3–7.0) months. 30 patients (15 F; 37.6±13.7 years) with intestinal CD who then developed PD were also identified (49 episodes of perianal sepsis). Of these, 9 had PD at presentation and in the remainder it was first manifest after a median of 41.3 (17.6–90.4) months from diagnosis. Conclusion: 8% of patients presenting with PD in this cohort went on to develop intestinal CD, which became evident shortly after surgical intervention. It is more common for patients with established CD to develop perianal disease and some do this after years of intestinal disease only.